Biopolymeric encapsulation system to protect and controlled gasstrointestinal passage of Lactobacillus acidophilus (TISTR 2365) - Sundarsingh, Anjelina; Anal, Anil Kumar; Loc Thai Nguyen; Bhujel, Ram C.; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
To promote the viability of L. acidophilus (TISTR 2365) at harsh conditions, hydrogel beads were formulated using sodium alginate (SA), whey protein isolate (WPI) and resistant starch (RS) to encapsulate the above-mentioned probiotic. Probiotic cells were successfully encapsulated with a highest encapsulation efficiency of 97.66±0.82 being achieved. The hardness, which is considered as an important criterion in the control release of the entrapped probiotic was found to be increased as the WPI concentration increased and with rather interference of RS, it was found to be decreasing making it more fragile as compared to SA-WPI hydrogel beads. The SEM images of the SA-WPI-RS hydrogel beads confirmed the successful entrapment of Lactobacillus acidophilus in the biopolymer matrix. The viability of L. acidophilus encapsulated in SA-WPI-RS matrix was higher as compared to free cells. The log reduction in 4.0 pH was found to be less as compared to others. The high thermal stability was acquired due to the presence of SA and RS in the of hydrogel beads. The viability was observed to be better at the end of 3 mins at 72C as compared to 63 (for 15 min) and 95C(30mins). A log reduction of 4.45 log CFU/mL was found in sample A1W6R4 as compared to free cell (7.53 log CFU/mL) in simulated gastric condition and a log reduction of 2.18 was observed in simulated intestinal condition in the same. Visual disintegration was observed in the sample under storage for 15 days in phosphate buffer solution of pH 7.2. This study showed that the SA-WPI-RS hydrogel beads can be used to encapsulate probiotics with high efficiency and are stable at harsh environments e.g. low acid and high heat conditions.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Food Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2020
Keywords: Probiotics; Encapsulation; Lactobacillus acidophilus